Convergence of human brain mapping tools: Neuronavigated TMS Parameters and fMRI activity in the hand motor area - Sarfeld, Anna‐Sophia (Hum Brain Mapp, 2011)
Functional magnetic resonance imaging (fMRI) and transcranial magnetic stimulation (TMS) are well‐established tools for investigating the human motor system in‐vivo. We here studied the relationship between movement‐related fMRI signal changes in the primary motor cortex (M1) and electrophysiological properties of the hand motor area assessed with neuronavigated TMS in 17 healthy subjects. The voxel showing the highest task‐related BOLD response in the left hand motor area during right hand movements was identified for each individual subject. This fMRI peak voxel in M1 served as spatial target for coil positioning during neuronavigated TMS. We performed correlation analyses between TMS parameters, BOLD signal estimates and effective connectivity parameters of M1 assessed with dynamic causal modeling (DCM). The results showed a negative correlation between the movement‐related BOLD signal in left M1 and resting as well as active motor threshold (MT) obtained for left M1. The DCM analysis revealed that higher excitability of left M1 was associated with a stronger coupling between left supplementary motor area (SMA) and M1. Furthermore, BOLD activity in left M1 correlated with ipsilateral silent period (ISP), i.e. the stronger the task‐related BOLD response in left M1, the higher interhemispheric inhibition effects targeting right M1. DCM analyses revealed a positive correlation between the coupling of left SMA with left M1 and the duration of ISP. The data show that TMS parameters assessed for the hand area of M1 do not only reflect the intrinsic properties at the stimulation site but also interactions with remote areas in the human motor system. Hum Brain Mapp, 2011. © 2011 Wiley‐Liss, Inc.